KEVALIDAN MEDIA PEMBELAJARAN BERBASIS LOGO BOARD GAMES MATERI SISTEM REPRODUKSI KELAS XI MIA - Muh. Teguh Iman Alhakim; Muh. Khalifah Mustami; Eka Damayanti (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
This is a research and development under some purposes, those are 1) To develop Logo Games Based for learning process on reproduction system material, 2) To know the validity of the Logo Board Games in learning process of reproduction system material. Logo Board Games is a media which is used to create an enjoyable learning situation and to support the achievement of learning objectives including the aspect of cognition, affection, and psychomotor. It is a research and development to produce a learning media “Logo Board Games” as the product which is expected to be used in encouraging the learning process. This research refers to 4-D learning model including four steps: defining, designing, developing, and disseminating. The research instruments utilized in this research was validation sheet to obtain the validity of the product, and questionnaire to know the response of the teachers and the students related to the effectiveness of the product. Based on the evaluation of the validator, it could be concluded that the validity of the Logo Board Games on reproduction system material could be categorized into high validity with the average grade 3,6 (3,5 ≤ V ≤ 4).